Implementasi Kebijakan Subsidi Listrik Tepat Sasaran bagi Rumah Tangga Tidak Mampu di Kecamatan Lubuk Begalung - Algamar, Ratika; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
Based on the Minister of Energy and Mineral Resources Regulation No. 29 of 2016, the mechanism for providing electricity tariff subsidies for households is regulated. In this case, the government has allocated a budget for electricity subsidies to customers, most of whom fall into the R1-450 VA and R1-900 VA categories, which account for about 85 percent of the total customers. The state has the obligation to subsidize electricity consumption for underprivileged communities. This study aims to examine the implementation of the electricity subsidy policy in Lubuk Begalung Subdistrict, focusing on whether it is effectively targeted, and the impact felt by low-income households regarding this subsidy policy. According to Dunn, policy implementation is a crucial stage in the public policy cycle. Dunn's implementation theory includes the complexity of implementation, actor interaction, local context, and implementation capacity. This study uses a qualitative approach. The results indicate that in the implementation of the targeted electricity subsidy policy for low-income households in Lubuk Begalung Subdistrict, Padang City, there are still low-income households that have not received electricity subsidies, while households suspected of being financially capable are receiving them. Additionally, the lengthy administrative registration process and the misuse of the intended purpose of the electricity subsidy policy were identified as issues.